Revascularization versus medical therapy for renal-artery stenosis. - Wheatley, K; Ives, N; Gray, R; Kalra, P; Moss, J; Baigent, C; Carr, S; Chalmers, N; Eadington, D; Hamilton, G; Lipkin, G; Nicholson, A; et al. (2009)
BACKGROUND: Percutaneous revascularization of the renal arteries improves patency in atherosclerotic renovascular disease, yet evidence of a clinical benefit is limited. METHODS: In a randomized, unblinded trial, we assigned 806 patients with atherosclerotic renovascular disease either to undergo revascularization in addition to receiving medical therapy or to receive medical therapy alone. The primary outcome was renal function, as measured by the reciprocal of the serum creatinine level (a measure that has a linear relationship with creatinine clearance). Secondary outcomes were blood pressure, the time to renal and major cardiovascular events, and mortality. The median follow-up was 34 months. RESULTS: During a 5-year period, the rate of progression of renal impairment (as shown by the slope of the reciprocal of the serum creatinine level) was -0.07x10(-3) liters per micromole per year in the revascularization group, as compared with -0.13x10(-3) liters per micromole per year in the medical-therapy group, a difference favoring revascularization of 0.06x10(-3) liters per micromole per year (95% confidence interval [CI], -0.002 to 0.13; P=0.06). Over the same time, the mean serum creatinine level was 1.6 micromol per liter (95% CI, -8.4 to 5.2 [0.02 mg per deciliter; 95% CI, -0.10 to 0.06]) lower in the revascularization group than in the medical-therapy group. There was no significant between-group difference in systolic blood pressure; the decrease in diastolic blood pressure was smaller in the revascularization group than in the medical-therapy group. The two study groups had similar rates of renal events (hazard ratio in the revascularization group, 0.97; 95% CI, 0.67 to 1.40; P=0.88), major cardiovascular events (hazard ratio, 0.94; 95% CI, 0.75 to 1.19; P=0.61), and death (hazard ratio, 0.90; 95% CI, 0.69 to 1.18; P=0.46). Serious complications associated with revascularization occurred in 23 patients, including 2 deaths and 3 amputations of toes or limbs. CONCLUSIONS: We found substantial risks but no evidence of a worthwhile clinical benefit from revascularization in patients with atherosclerotic renovascular disease. (Current Controlled Trials number, ISRCTN59586944.)